The Possibility of Marcus Gunn Jaw-winking and Monocular Elevation Deficiency Being the Same Disease - Sogand Shahabinia; Reza Jafari; Somayeh Rostami Maskopaii (Mazandaran University of Medical Sciences, 2020)
Introduction: Marcus Gunn Jaw-Winking (MGJW) synkinesis is characterized by drooping eyelid and retraction with jaw movement. MGJW is usually seen alone, although familial cases have been documented. One of the problems that may occur with MGJW is Monocular Elevation Deficiency (MED). The concomitant MGJW, congenital ptosis, and MED represent a congenital misdirection syndrome that involves oculomotor nerve.  Case Presentation: In this report, we present a 13-year-old girl with MGJW with severe ptosis and concomitant MED in her left eye. A brief review was performed about this case too. Conclusions: MED and MGJW maybe two extremes of one disease, because there is of a high probability of the same inheritance in the two conditions (both are due to a gene defect). Also, in our case with more severe ptosis, MED appeared, while in her aunt with less ptosis and milder MGJW, MED was absent.